Does pragmatic beat syntax? Evidence from focus accent placement in the semi-spontaneous speech of Italian learners of German - Vogt, Barbara; Paschke, Peter (Linguistik Online, 2018)
In this paper, we investigate the prosodic marking of information structure by Italian L1 learners of German. We analyze two different contexts with non-final focus accents, i. e. narrow and broad focus contexts, mainly on sentence level while most studies discussing post-focal de-accentuation are restricted to noun phrases. For Italian learners, non-final placement of focus accents is likely to cause problems, given that in their L1, phonetic prominence is normally as-signed to the last constituent in the verbal phrase. Our initial hypothesis was that the hypothetical "cognitive universal" requiring de-accentuation of given elements might probably guide the learners in realizing the correct pitch contour in contexts with a non-final narrow focus (and pragmatic de-accentuation of the final given constituent). By contrast, the de-accentuation of phrase-final lexical verbs in broad focus contexts was expected to cause more problems given that this typologically marked syntactic structure does not exist in Italian. However, in a previous study based on read speech, de-accentuation of final given elements was managed by inter-mediate Italian learners of German L2 only slightly better than realizing a non-final focus accent in all new contexts on the argument in OV structures (success rate of 55% vs. 48%, with no statistically significant difference). In other words, both types of non-final focus accents seem to be balanced at this intermediate stage of acquisition. In this contribution, our goal is to discover whether in semi-spontaneous speech one can find the same distributional patterns of non-final focus accents in this learner variety of Italian learners of German. To this end, we analyzed recordings of oral exams from the same 10 Italian university students that had taken part in the previous study. The analysis shows that in semi-spontaneous speech production too, there is evidence for the hypothesis that pragmatics does not "beat" syntax in prosodic acquisition. Besides, when the two different data types were compared, a very high intra-speaker correlation emerged between read and semi-spontaneous speech.